SIFAT MEKANIS LAMINASI LENGKUNGAN BAMBU BETUNG (Dendrocalamus asper (Schulters f.) Backer ex Heyne) dan TALI (Gigantochloa apus (J.A. & J.H. Schultes) Kurz). - Noermalicha Noermalicha (Universitas Trisakti, 2007)
AbstractPreface study shows a possibility of bamboo to be bent and also proves that species affects to the results of mechanical properties. Bamboo was bent with the radius of curvature of 28 CM, as an example, used PVAc (industrial specification), and _formed manually in cold pressed at pressure setting at room temperature for 24 hours. In order to examine the best composition of optimal laminate effect, influence of node existing, and effect of shape; 24 samples of 2 cm x 2 cm x 30 cm were made and three replicates were prepared. In order to compare species influence were selected Dendrocalamus asper (Schultes f) Backer ex Heyne and Gigantochloa apus (J.A. & Schultes) Kurz that have different anatomical structure.Results indicate that node presence not significantly affects mechanical properties of Betting bamboo but significantly for Tali bamboo. To get the optimum mechanical properties, thickness of laminate is about 4 mm to 5 min. Decreasing of mechanical properties of laminated bended bamboo is not caused by node presence but by shape influence. The modulus of elasticity (MOE) value of Belling bamboo is decreasing almost 50% from the mechanical properties. Meanwhile, the MOE value of laminated straight bamboo of Tali decreases until 5 times from its mechanical properties, and the MOE value of laminated ['ended bamboo of decreases until 25% from laminated straight bamboo. Conversely, the modulus of rupture (MOR) of both of laminated bamboo is not significantly.